Demography, reproductive ecology, and variation in survival of greater sage‐grouse in northeastern California. Issue 8 (16th October 2014) - Davis, Dawn M.; Reese, Kerry P.; Gardner, Scott C.
ABSTRACT We examined demographic parameters and factors influencing nest survival of female greater sage‐grouse (Centrocercus urophasianus) in northeastern California. Additionally, we used known‐fate models in program MARK to examine bi‐weekly survival rates of females over an 8‐month period (Mar–Oct, 2007–2009). Nest survival rate, assuming a 38‐day exposure period, was 41% and was positively associated with grass height (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2ck7mg8p" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />βˆ</alternatives> = 0.03, SE = 0.02), but the 95% confidence interval overlapped 0 (95% CI = −0.007–0.767) and the effect of grass height on nest success was likely to be small. Grass height and visual obstruction was greater at nest sites than at random locations, suggesting females selected sites with structurally more closed habitat for nesting. Females that nested under vegetation other than sagebrush (Artemisia spp.) had increased nest survival probabilities, suggesting sage‐grouse selection of nest sites is based on vegetation structure more than plant species. Sagebrush canopy cover was considerably lower in our study area (approx. 10% on random plots) compared with sagebrush cover described across the geographic range of sage‐grouse (>15%) and sage‐grouse use of non‐sagebrush plants in our study suggests sagebrush nesting habitat is limited. The overall 8‐month survival (breeding season through autumn migration) for female sage‐grouse was 49% (SE = 0.06) with most deaths occurring in spring and autumn. Mortalities during spring coincided with nest initiation, incubation, and following hatch when successfully nesting females were tending to chicks. Mortalities in September coincided with dispersal and autumn migration. The survival estimate during the breeding season was greater among known failed nesters (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2ck7mg97" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />SˆFAILED</alternatives> = 0.69) than females that nested successfully (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2ck7mg6k" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />SˆSUCCESSFUL</alternatives> = 0.53), indicating female greater sage‐grouse were exposed to greater mortality risk during incubation and brood‐rearing periods. Greater mortality risk during the breeding season (i.e., nesting and brood‐rearing) can have a major impact on greater sage‐grouse demography. Conservation and management efforts should focus on enhancing female greater sage‐grouse survival during the breeding and brood‐rearing season. © 2014 The Wildlife Society.